JIHAD AND JUST WAR - Spoerl, Joseph (The Levantine Review, 2013)
This paper attempts to demonstrate that the differences between the Western and Islamic traditions on the ethics of warfare run far deeper than what traditional scholarship suggests. The present study focuses on three main areas: the sources of our knowledge of morality, the objectives of warfare, and the principle of non-combatant immunity. We shall see that these three topics are inter-connected, and also that understanding the classical Islamic law of war is essential to understanding the ideology and allure of contemporary Islamism.